A New Efficient Method for Nonlinear Fisher-Type Equations - Hossein Aminikhah; Farshid Mehrdoust; Ali Jamalian (Journal of Applied Mathematics)
Laplace transform and new homotopy perturbation methods are adopted to study Fisher-type equations analytically. The solutions introduced in this study can be used to obtain the closed form of the solutions if they are required. The combined method needs less work in comparison with the other homotopy perturbation methods and decreases volume of calculations considerably. The method is tested on various examples, and results show that new method is more effective and convenient to use, and high accuracy of it is evident.